Overseas teaching experience and motivational currents: The case of EFL pre-service teachers in Indonesia - Rasman, R. (Universitas Pendidikan Indonesia, 2018)
Motivational currents have recently gained popularity in research on psychology of language learners and teachers. This study aims to find out whether an overseas teaching program can (1) create motivational currents among Indonesian pre-service teachers and (2) help them build a vivid vision of being a language teacher. This research used retrodictive qualitative modelling (RQM) under a complex dynamic system (CDS) approach to trace back the factors that enabled the motivational currents to occur. The data were collected from semi-structured interviews along with day-to-day diaries of six EFL pre-service teachers in Indonesia. The findings suggest that the overseas teaching program could create motivational currents of three participants while the rest did not experience such intense motivation. This study also finds that there is a dynamic relationship between self-system and motivational currents system. The impact of experiencing the motivational currents on the vision of being a language teacher varies from one participant to another. This study is of great importance especially for teacher educators wishing to design meaningful and effective professional development activities for their student teachers.